The incredible journey eaudiobook - Burnford, Sheila (Listening Library, 2000)
Fans of Old Yeller , Where the Red Fern Grows , and Shiloh will love this timeless classic about two dogs and a cat that embark on a journey to return to their owner and inspired the movie Homeward Bound .    An inquisitive Labrador retriever, friendly bull terrier, and courageous Siamese cat set out through the Canadian wilderness to find their owner in this truly “incredible” adventure.     Instinct tells them that the way home lies to the west and together the three house pets face hunger, the natural elements, and wild forest animals as they make their way home to the family they love.     This beloved classic that inspired the movie Homeward Bound has captured the hearts of generations of readers. The lengths to which these three animals will go for each other and for their owner make for a thrilling and thoroughly unforgettable tale.   “ Captivating! A tale of charm [and] high drama.”— The New York Times   “ A classic. ”— The Atlantic “From the youngest child…to the oldest grown-up, there is something here for everyone .”— The Horn Book   "An incredible book! A beautiful story so moving that it stays in the mind constantly. It is a gem to be treasured."— The St. Louis Post-Dispatch "I have read The Incredible Journey with much enjoyment. Obviously the author has a great knowledge of animals and a great love for them. "—Joy Adamson, author of Born Free   “ A clever story and evocative writing will keep animal lovers and adventure fans turning the pages.”— Common Sense Media   Pacific Northwest Young Reader’s Choice Award Winner   William Allen White Award Winner   Dorothy Canfield Fisher Award Winner